NGEMBANGAN MATERI HUBUNGAN ANTAR PRIBADI BAGI SISWA SMA SEDERAJAT - Yori, Ritanti; Saam, Zulfan; ', Rosmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Not optimal student achievement one of them caused by low ability students in inter-personal relationships to each other. In that regard the school plays an important role in efforts to improve the ability of these interpersonal relationships, especially for students in school. But so far the school has not shown efforts to deal with such matters. Therefore, the researchers felt the need to develop a material on Personal Relationships Students are expected to be used by the teacher guidance and counseling to be delivered to students. This material is prepared using methods of research and development (R & D). The purpose of this research is 1) Establishment of Student Personal Relationships matter in terms of clarity, systematics, image support, freshness and completeness of the materials and support games / video 2) To determine the quality of material produced. This material is validated by the supervisor 1 & 2 teachers and 16 students Counseling Vocational Guidance and Counseling Labor Patronage Unri Pekanbaru. This material is tested to the student with the allocation of a 3-hour lessons (3 x 45 '). This material consists of a sense of personal relationships, the kind of personal relationships, a model of interpersonal relationships, the goal of establishing interpersonal relationships, the stages of interpersonal relationships, factors that affect interpersonal relationships and how to develop interpersonal relationships. The results of the development of this material indicates the quality of the material produced in the category